Population of Chironomidae (Insecta: Diptera) in UNIMAS Lake and its Potential as a Culture Speceies in Laboratory Condition - Nor Syuhaidah, Binti Mohammad Zee Hood (Universiti Malaysia Sarawak, (UNIMAS), 2014)
The study of chironomid populations and its relationship with water quality was conducted in UNIMAS Lake. The objectives of this study are to determine the density of chironomid larvae in UNIMAS Lake and its potential as culture species in the laboratory conditions. Sediments sampling were conducted by using Poinar Grab Sampler at four selected stations in the lake. The fish and prawn were caught for gut content analysis and live feed trial in the laboratory. Population of Chironomidae was nearly consistent within the UNIMAS Lake. Water parameters of pH, turbidity and chlorophyll a were significantly different between station with p-value = 0.000. Dissolved oxygen was found influenced the density of chironomid larvae in UNIMAS Lake. A number of fish species from UNIMAS Lake were discovered feed on bloodworm. Chironomidae has potential to be reared in laboratory condition with salinity and temperature as factors for prolongation of larvae stage.